Proceedings of the 48th International Symposium on Microarchitecture 2015
DOI: 10.1145/2830772.2830797
|View full text |Cite
|
Sign up to set email alerts
|

Rubik

Abstract: Latency-critical workloads (e.g., web search), common in datacenters, require stable tail (e.g., 95th percentile) latencies of a few milliseconds. Servers running these workloads are kept lightly loaded to meet these stringent latency targets. This low utilization wastes billions of dollars in energy and equipment annually.Applying dynamic power management to latency-critical workloads is challenging. The fundamental issue is coping with their inherent short-term variability: requests arrive at unpredictable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Many important cloud workloads are latency-critical, and they require strict levels of quality-of-service (QoS) to meet user expectations [15][16][17]. A web-search, for example, must complete within a fraction of a second [18], otherwise users are likely to give up and leave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many important cloud workloads are latency-critical, and they require strict levels of quality-of-service (QoS) to meet user expectations [15][16][17]. A web-search, for example, must complete within a fraction of a second [18], otherwise users are likely to give up and leave.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works [15][16][17][21][22][23] have shown that traditional power management practices and CPU utilization measures are unsuitable to drive task management for data center workloads. This is because prior schemes (like OS-level DVFS) work well to deliver long-term performance for batch workloads, but they can severely hurt the QoS of latency-critical data center workloads.…”
Section: Introductionmentioning
confidence: 99%
“…Both these forms present a challenge for a heuristic based approach as it jumps across multiple con gurations to meet the QoS target, thereby leading to QoS violations due to rampant core oscillations. Also, the authors of Rubik [36] note that core-transitions are far more costly relative to DVFS changes.…”
Section: Exploring Individual Workload Particularitiesmentioning
confidence: 99%
“…HipsterIn performs well because it moves directly to the appropriate core con guration for a given load that satis es QoS. In addition to switching between a combination of di erent cores, HipsterIn also explores more ne-grained DVFS adaptations, which has lower overheads (of microseconds) compared with migrations between cores (order of milliseconds) [36].…”
Section: Hipster's Heuristic Policy (Interactive Only)mentioning
confidence: 99%
See 1 more Smart Citation